Density-based separation performance of a secondary air-distribution fluidized bed separator (SADFBS) for producing ultra-low-ash clean coal. (15th May 2016) - He, Jingfeng; Tan, Mingbing; Zhu, Ran; Zhao, Yuemin; Hong, Pu; Jiang, Yong
Highlights: A secondary air-distribution fluidized bed was used to produce ultra-low-ash clean coal. Operational factors were determined by verifying bed stability and density uniformity. Response surface methodology was used to evaluate the significance of various factors. Abstract: Stable fluidization with consistent flow and a reasonable separating density are keys to the highly efficient separation in a secondary air-distribution fluidized bed separator (SADFBS). In this study, a binary dense medium was formed by mixing fine coal with magnetite powders. The optimum secondary air-distribution layer (SAL) height of 13 mm was obtained by verifying the density uniformity of the bed. The suitable static bed height of 60–100 mm was determined by comparing the fluctuation of bed pressure drops. In addition, the distribution characteristics of the fine coal particles in various bed layers indicated that the feeding fine coal content should be not more than 10%, which was verified by the bubbling performance in the bed. Box–Behnken Response Surface Methodology (BB-RSM) was employed to evaluate the effects of static bed height ( Hs ), fluidization number ( N ), and feeding fine coal content ( P ) on the combustible material recovery θ of feed coal. Based on the experimental data, a mathematical model was established to describe the relationship between combustible material recovery and the operational factors. The influential degree of various factors on θ was N  >  Hs  >  P . The separation results of SADFBS suggested that θ value was maximized when Hs  = 100 mm, N  = 1.45, and P  = 4%, which showed a good separation performance. The ash content of clean coal reached the lowest value of 2.65% when Hs  = 80 mm, N  = 1.70 and P  = 7%, with a yield of 64.89% and a combustible material recovery of 74.86%. The product is generally considered to be ultra-low-ash clean coal which is the raw materials for activated carbon production.